21 things you may not know about the Indian Act - Joseph, Robert P. C., 1963- (Port Coquitlam, B.C. : Indigenous Relations Press, 2018)
"Based on a viral article, 21 Things You May Not Know About the Indian Act is the essential guide to understanding the legal document and its repercussion on generations of Indigenous peoples, written by a leading cultural sensitivity trainer. The Indian Act, after 141 years, continues to shape, control, and constrain the lives and opportunities of Indigenous peoples, and is at the root of many lasting stereotypes. Bob Joseph's book comes at a key time in the reconciliation process, when awareness from both Indigenous and non-Indigenous communities is at a crescendo. Joseph explains how Indigenous peoples can step out from under the Indian Act and return to self-government, self-determination, and self-reliance-and why doing so would result in a better country for every Canadian. He dissects the complex issues around truth and reconciliation, and clearly demonstrates why learning about the Indian Act's cruel, enduring legacy is essential for the country to move toward true reconciliation."
Includes bibliographical references and index.
NAT ak
Keywords: Canada; Indigenous peoples -- Legal status, laws, etc. -- Canada; Indigenous peoples -- Canada -- Government relations; Indigenous peoples -- Canada -- Politics and government; First Nations -- Legal status, laws, etc; First Nations -- Canada -- Government relations; First Nations -- Canada -- Politics and government; Professional collection